2011
DOI: 10.1158/0008-5472.can-11-0773
|View full text |Cite
|
Sign up to set email alerts
|

Modification of BRCA1-Associated Breast and Ovarian Cancer Risk by BRCA1-Interacting Genes

Abstract: Inherited BRCA1 mutations confer elevated breast cancer risk. Recent studies have identified genes that encode proteins that interact with BRCA1 as modifiers of BRCA1-associated breast cancer. We evaluated a comprehensive set of genes that encode most known BRCA1 interactors to evaluate the role of these genes as modifiers of cancer risk. A cohort of 2,825 BRCA1 mutation carriers was used to evaluate the association of haplotypes at ATM, BRCC36, BRCC45 (BRE), BRIP1 (BACH1/FANCJ), CTIP, ABRA1 (FAM175A), MERIT40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 25 publications
2
33
1
Order By: Relevance
“…Recent studies suggest that certain mutations or polymorphisms in the RAP80, ABRA1, or MERIT40/NBA1 (another member of the RAP80 complex) genes are associated with increased susceptibility to breast and/or ovarian cancer (75-80). In addition, the genomic region containing the RAP80 gene is not infrequently lost in TNBCs, which commonly exhibit gross manifestations of genomic instability (81).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that certain mutations or polymorphisms in the RAP80, ABRA1, or MERIT40/NBA1 (another member of the RAP80 complex) genes are associated with increased susceptibility to breast and/or ovarian cancer (75-80). In addition, the genomic region containing the RAP80 gene is not infrequently lost in TNBCs, which commonly exhibit gross manifestations of genomic instability (81).…”
Section: Discussionmentioning
confidence: 99%
“…DSBs activate a DNA damage response (DDR) that coordinates the activation of cell cycle checkpoints, apoptosis, and DNA repair networks, to ensure accurate repair and genomic integrity. Defects in DNA repair mechanisms are associated with various human developmental and immune disorders and an increased cancer risk (25). …”
Section: Introductionmentioning
confidence: 99%
“…Its role in DDR and the potential link between RAP80 mutations and human mammary and ovarian cancer, suggested that defective RAP80 function/expression might result in genomic instability and increased cancer risk (5, 21). In this study, we investigated the effect of the loss of RAP80 expression on genomic stability and cancer development in RAP80 −/− mice using several tumorigenesis models, including IR-induced lymphoma and 7,12-dimethylbenz(a)anthracene (DMBA)-induced mammary cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have assessed the role of the most common ATM variants in breast cancer susceptibility, the results obtained are inconsistent [35]. A recent study had identified an association between an ATM haplotype and breast cancer risk in BRCA1 mutation carriers with a false discovery rate-adjusted p value of 0.029 for overall association of the haplotype [36]. Four of the five SNPs making up the haplotype were almost perfectly correlated ( r 2 >0.9) with the three originally genotyped SNPs of the present study.…”
Section: Discussionmentioning
confidence: 99%